Microstructure and Mechanical Properties of Laser-Clad Inconel 718 Coatings on Continuous Casting Mold Copper Plate - Yu Liu; Haiquan Jin; Guohui Li; Ruoyu Xu; Nan Ma; Hui Liang; Jian Lin; Wenqing Xiang; Zhanhui Zhang (Lubricants, 2025)
Mold copper plates (Cr–Zr–Cu alloy) frequently fail due to severe wear under high-temperature conditions during continuous casting. To solve this problem, Inconel 718 coatings were prepared on the plate surface via laser cladding to enhance its high-temperature wear resistance. The results demonstrate that the coatings exhibit a defect-free structure with metallurgical bonding to the substrate. The coating primarily consists of a γ-(Fe, Ni, Cr) solid solution and carbides (M23C6 and M6C). Notably, elongated columnar Laves phases and coarse Cr–Mo compounds were distributed along grain boundaries, significantly enhancing the coating’s microhardness and high-temperature stability. The coating exhibited an average microhardness of 491.7 HV0.5, which is approximately 6.8 times higher than that of the copper plate. At 400 °C, the wear rate of the coating was 4.7 × 10−4 mm3·N−1·min−1, significantly lower than the substrate’s wear rate of 8.86 × 10−4 mm3·N−1·min−1, which represents only 53% of the substrate’s wear rate. The dominant wear mechanisms were adhesive wear, abrasive wear, and oxidative wear. The Inconel 718 coating demonstrates superior hardness and excellent high-temperature wear resistance, effectively improving both the surface properties and service life of mold copper plates.